2022
DOI: 10.1039/d2cp03464f
|View full text |Cite
|
Sign up to set email alerts
|

Polyanionic cyano-fullerides for CO2 capture: a DFT prediction

Abstract: The reaction of C60 fullerene with ‘n’ molecules (n = 1 to 6) of 1,3-dimethyl-2,3-dihydro-2-cyano-imidazole (IMCN) results in the exothermic formation of imidazolium cation-polyanionic fulleride complexes, (IM+)n…((C60(CN)n)n–). The binding energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In a recent study, we have shown that anionic cyano derivatives of C 60 are promising systems for CO 2 capture. 39 The study also showed that the incorporation of the solvation effect on the formation of cyanofullerides showed a more exothermic character to the reactions. Hence the solvation is expected to stabilize the complexes of the N-doped cyanofullerides as well.…”
Section: N-doped Cyanofullerides For Co 2 Adsorptionmentioning
confidence: 89%
See 2 more Smart Citations
“…In a recent study, we have shown that anionic cyano derivatives of C 60 are promising systems for CO 2 capture. 39 The study also showed that the incorporation of the solvation effect on the formation of cyanofullerides showed a more exothermic character to the reactions. Hence the solvation is expected to stabilize the complexes of the N-doped cyanofullerides as well.…”
Section: N-doped Cyanofullerides For Co 2 Adsorptionmentioning
confidence: 89%
“…The previous study on (C 60 CN) À has shown both noncovalent and covalent interactive behaviour of CO 2 with the carbon cage of fullerides. 39 The carbon cage of the (C 60À2n N 2n CN) À systems also interact with CO 2 through either noncovalent CÁ Á ÁC interactions or a strong covalent C-C bond interactions (Fig. 9).…”
Section: N-doped Cyanofullerides For Co 2 Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the level of academic research, various classes of chemical compounds and materials are screened to identify and characterize potentially useful and tunable physicochemical properties. [8][9][10][11][12] Both physical and chemical sorption of CO 2 represent a practical interest. [13][14][15][16][17][18] The current chemisorption solutions are preferentially based on the formation of a carbon-nitrogen covalent bond (viz., alkyl amines and derivatives) and strong oxygen-metal ionic bonds (viz., carbonate looping).…”
Section: Introductionmentioning
confidence: 99%
“…At the level of academic research, various classes of chemical compounds and materials are screened to identify and characterize potentially useful and tunable physicochemical properties. 8–12…”
Section: Introductionmentioning
confidence: 99%